2016
DOI: 10.2147/ijn.s96614
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds coupled with 5,7-dimethoxycoumarin, a plant bioactive metabolite, interfere with the mitotic process in B16F10 cells altering the actin organization

Abstract: For the first time, we coupled reduced detonation nanodiamonds (NDs) with a plant secondary metabolite, citropten (5,7-dimethoxycoumarin), and demonstrated how this complex was able to reduce B16F10 tumor cell growth more effectively than treatment with the pure molecule. These results encouraged us to find out the specific mechanism underlying this phenomenon. Internalization kinetics and quantification of citropten in cells after treatment with its pure or ND-conjugated form were measured, and it was reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…4 F-NDP as a platform are capable of diverse functionalization and have been coupled to antibodies for protein detection, adsorbed with small molecules for therapeutic purposes, and even inorganically doped for use as catalysts. [5][6][7] Our previous set of in vitro studies, in which we demonstrated the specific association of the F-NDP NVN -Bit with platelets embedded within plasma clot generated by thrombin-activated rat platelet-rich plasma, provided a first-line "proof of feasibility" for our concept. 4 Since transmission of light across biological tissues is subject to interferences (scatter, absorption, diffraction) by organic and inorganic materials of the tissues, 8 we have primarily focused on the near-infrared (NIR) optical window, which significantly facilitates penetration of light through biological tissues.…”
mentioning
confidence: 83%
“…4 F-NDP as a platform are capable of diverse functionalization and have been coupled to antibodies for protein detection, adsorbed with small molecules for therapeutic purposes, and even inorganically doped for use as catalysts. [5][6][7] Our previous set of in vitro studies, in which we demonstrated the specific association of the F-NDP NVN -Bit with platelets embedded within plasma clot generated by thrombin-activated rat platelet-rich plasma, provided a first-line "proof of feasibility" for our concept. 4 Since transmission of light across biological tissues is subject to interferences (scatter, absorption, diffraction) by organic and inorganic materials of the tissues, 8 we have primarily focused on the near-infrared (NIR) optical window, which significantly facilitates penetration of light through biological tissues.…”
mentioning
confidence: 83%
“…Nanomaterials, which measure 1–1,000 nm, have unique physical and chemical properties such as small-size effect, large surface area, high reactivity, and quantum effects. In addition, they have been certified as breaking a new ground in disease detection,8,9 imaging,10,11 diagnosis,12,13 and treatment 12,1416. Carbon-based nanoparticles are an important part of nanomaterials; they include carbon nanotubes, fullerene, and graphene and its derivatives 17.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Recently, biotechnological application of nanomaterials conjugated with plant molecules has been continuously gaining importance in the therapeutic and medical field. 25,26 Nanomaterials used as carriers of plant secondary metabolites are characterized by chemical stability, octahedral symmetry, rigid structure, large surface area, and low cost of production. 26 Studies suggest that quercetin, an important flavonoid antioxidant thought to promote health, partly due to its ability to act as an antioxidant against ROS, helps in maintaining the blood pressure, fighting asthma and allergies, preventing angiocardiopathy and tumor progression, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Nanomaterials used as carriers of plant secondary metabolites are characterized by chemical stability, octahedral symmetry, rigid structure, large surface area, and low cost of production. 26 Studies suggest that quercetin, an important flavonoid antioxidant thought to promote health, partly due to its ability to act as an antioxidant against ROS, helps in maintaining the blood pressure, fighting asthma and allergies, preventing angiocardiopathy and tumor progression, and so on. [27][28][29][30][31][32][33] Indeed, quercetin as a well-known flavonoid with various biological effects has been widely used in many disease models.…”
Section: Introductionmentioning
confidence: 99%